ANALISIS KOMPETENSI, DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA KARYAWAN STUDI PADA BADAN PENAGGULANGAN BENCANA DAERAH DIY - Yogi saputra; Ignatius Soni Kurniawan (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2021)
This study aims to determine the effect of competence, work discipline and work experience on employee performance on disaster management staff in the Special Region of Yogyakarta. This study uses a saturated sample with a population of 43 respondents. Data collection techniques in this study used a questionnaire with a census. The data analysis method used the classical assumption test, multiple linear test and the coefficient of determination test. The results of this study indicate that the competence variable has a positive and significant effect on employee performance, the work discipline variable has a positive and significant effect on employee performance and the work experience variable has a positive and significant effect on employee performance, simultaneously the variables competence, work discipline and work experience have a positive effect. and significant to employee performance. urgent. significant to employee performance. Keywords: Competence, Work Discipline, Work Experience, Employee Performance.